БИОЛОГИЯ ФАНЛАРИНИ ЎҚИТИШДА НОСТАНДАРТ ТЕСТ ТОПШИРИҚЛАРИДАН ФОЙДАЛАНИШ МАСАЛАЛАРИ - Ешмуратов, Р.А.; Сапарниязов, И.А. (SCIENCE and SOCIETY, 2017)
The article deals with the issues of using nonstandard test, for the control and assessment of students’ knowledge in the studying process in some subjects in Biology.